The transcriptome pattern of liver, spleen and hypothalamus provides insights into genetic and biological changes in roosters in response to castration - Li, Wenpeng; Li, Hui; Yan, Chao; Chen, Siyu; Zhao, Xingbo (Frontiers in Genetics, 2022)
Chicken is widely accepted by consumers because of its delicate taste and abundant animal protein. The rooster after castration (capon) is believed to show better flavor, however, the molecular changes of the underpinned metabolism after castration is not yet understood. In this study, we aimed to figure out the alternation of meat quality and underpinned molecular mechanism via transcriptomic profiling of liver, spleen and hypothalamus as targeted organs in response to the castration. We identified differential expressed genes and their enriched functions and pathways in these organs between capon and rooster samples through RNA-seq analysis. In the liver, the lipid metabolism with targeted FABP1gene was found significantly enriched, which may be as one of the factors contributing to increased fat deposition and thus better meat flavor in capons than roosters, as predicted by the significantly lower shear force in capons than in roosters in meat quality experiments. However, the ability to xenobiotic detoxification and excretion, vitamin metabolism, and antioxidative effect of hemoglobin evidenced of the capon may be compromised by the alternation of SULT, AOX1, CYP3A5, HBA1, HBBA, and HBAD. Besides, in both the spleen and hypothalamus, PTAFR, HPX, CTLA4, LAG3, ANPEP, CD24, ITGA2B, ITGB3, CD2, CD7 and BLB2 may play an important role in the immune system including function of platelet and T cell, development of monocyte/macrophage and B cell in capons as compared to roosters. In conclusion, our study sheds lights into the possible molecular mechanism of better meat flavor, fatty deposit, oxidative detoxification and immune response difference between capons and roosters.